HUBUNGAN TINGKAT PENGETAHUAN DENGAN SIKAP IBU POST PARTUM TENTANG TEKNIK MENYUSUI YANG BAIK DAN BENAR PADA BAYI USIA 0-6 BULAN DI PMB HIKMAHWATI KABUPATEN BARITO KUALA - Ningsih, Agus Sulistyo (STIKES Suaka Insan, 2023)
Background: Exclusive breastfeeding is giving only breast milk for six months without giving additional food and other drinks such as formula milk, juice or food. Breast milk is the most important food for babies, especially the first months of life. ASI is an ideal source of nutrition with a balanced composition and in accordance with the needs of the baby's growth. Breastfeeding can increase the baby's immunity so that it can reduce infant mortality. Purpose : The purpose of this study was to determine the relationship between Knowledge and Attitudes of Post Partum Mothers regarding Good and Correct Breastfeeding Techniques for Babies Aged 0-6 Months at PMB Hikmahwati, Amd.keb, Batola Regency in 2022. Research methods: The method in this study was correlational. Sampling was taken using the total sampling technique, with the number of respondents breastfeeding post partum mothers at PMB Hikmahwati, Amd.keb in September-December 2022 as many as 30 respondents. The instrument used in this study was a questionnaire that had been tested for validity and reliability. The analysis used in this study was univariate analysis. Data were analyzed with statistical testschisquare with an error rate of 0.05. Research result: Based on the results of research at PMB Hikmahwati, Amd.Keb Based on the use of statistical test results obtained <p 0.05, so there is a significant relationship between the attitude of post partum mothers and good and correct breastfeeding techniques. Conclusion: It can be concluded that there is a relationship between knowledge and attitudes of post partum mothers regarding proper and proper breastfeeding techniques for infants aged 0-6 months at PMB Hikmahwati, Amd.Keb. Keywords :knowledge, attitudes, breastfeeding techniques